Efficiency of Criminal Proceedings, Judicial Reform and Accession Negotiations With EU - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
The failed attempt to reform the criminal proceedings legislation during 2006 significantly delayed the transition to a prosecutorial investigation and establishing normative framework preconditions for improving the efficiency of the criminal proceedings. After the catastrophic intervention due to the organisation of the judiciary in 2009, judicial and organisational capacity to promptly conduct criminal proceedings has been reduced to a minimum. The problem culminated after the cardinal reform that brought the Code of Criminal Procedure in 2011. The need for a systemic response to the situation of the growing backlog of more frequent cases and the European Court of Human Rights for the violation of the right to trial within a reasonable time has been recognised in the National Judicial Reform Strategy for the period 2013–2018. Further reforms in this area are largely conditioned by the process of accession negotiations with the EU under Chapter 23.